Mer Tyrosine Kinase (MERTK) modulates liver fibrosis progression and hepatocellular carcinoma development - Pipitone, Rosaria Maria; Calvaruso, Vincenza; Di Marco, Lorenza; Di Salvo, Francesca; Gaggianesi, Miriam; Lupo, Giulia; Zito, Rossella; La Mantia, Claudia; Ramazzotti, Matteo; Petta, Salvatore; Di Marco, Vito; Craxì, Antonio; et al. (Frontiers in Immunology, 2022)
Abstract Background: MerTK is a tyrosine kinases receptor that belongs to tumor-associated macrophages family. It is involved in different processes including cellular proliferation/survival, cellular adhesion/migration, and release of the inflammatory/anti-inflammatory cytokines. Although it is reported that MERTK polymorphisms affect the severity of viral and metabolic liver diseases, being able to influence fibrosis progression and hepatocellular carcinoma development, the mechanisms remain unknown. Methods: using a microarray approach, we evaluated the liver expression of genes involved in fibrogenesis and hepatocarcinogenesis in patient with chronic hepatitis C (CHC), stratified for MERTK genotype and MERTK expression. Results: we found that the rs 4374383 AA homozygosity is associated with lower MERTK expression in CHC patients and that, depending on MerTK genotype, Matrix Metallopeptidase 9 (MMP9), Matrix Metallopeptidase 7 (MMP7), Secreted Frizzled Related Protein 1 (SFRP1) and WNT gene family 11(WNT11) show differential expression in patients with CHC with or without neoplastic progression. Conclusions: our results confirm that MerTK represents a genetic biomarker for progression of liver disease and are suggestive of translational relevance for the study of downstream pathways involved in fibrogenesis and hepatocarcinogenesis.